The Role Of Foreign Direct Investment Inflow And Outflow In India’s Economic Growth - Kumar, Prashant; V.N.Gupta (International Journal of Economics (IJEC), 2025)
This study investigates the trends of Foreign Direct Investment (FDI) in India, focusing on both inflows and outflows as a percentage of GDP from 2000 to 2022. Foreign direct investment (FDI) has become a key driver of economic growth, shaping India’s integration into the global economy. This study employs econometric techniques such as autoregressive (AR) models, Moving Average (MA) models, the Johansen Co-integration Test, and the Granger Causality Test to analyze historical FDI data. These methods help evaluate the dynamic relationships and long-term equilibrium between FDI inflows and outflows. The analysis reveals that historical FDI patterns significantly predict future trends. Specifically, past values and forecast errors influence the direction of FDI, particularly outflow. The Johansen cointegration test confirms a long-term equilibrium relationship between inflows and outflows, while the Granger Causality Test identifies a predictive relationship between net outflows and inflows. The findings suggest that inward and outward FDI are interlinked and play vital roles in India's economic development. Understanding these dynamics can help policymakers craft strategies to enhance India's global investment, while sustaining domestic economic growth